How perceived scarcity predicted cooperation during early pandemic lockdown - Civai, Claudia; Caserotti, Marta; Carrus, Elisa; Huijsmans, Inge; Rubaltelli, Enrico (Frontiers in Psychology, 2022)
Both material resources (jobs, healthcare), and socio-psychological resources (social contact) decreased during the COVID-19 pandemic. We investigated whether individual differences in perceived material and socio-psychological scarcity experienced during the pandemic predicted preference for cooperation, measured using two Public Good Games (PGGs), where participants contributed money or time (i.e., hours indoors contributed to shorten the lockdown). Material scarcity had no relationship with cooperation. Increased perceived scarcity of socio-psychological wellbeing (e.g., connecting with family) predicted increased preference for cooperation, suggesting that missing social contact fosters prosociality, whilst perceived scarcity of freedom (e.g., limited movement) predicted decreased willingness to spend time indoors to shorten the lockdown. The importance of considering individual differences in scarcity perception to best promote norm compliance is discussed.